Kesetaraan Gender dalam Pendidikan Islam di Indonesia (Perspektif Nyai Siti Walidah dan Nyai Khairiyah Hasyim) - Syafitri Hayati Hsb; Radea Yuli A Hambali (Gunung Djati Conference Series, 2023)
This research is a type of qualitative research with a literature study approach in which, in collecting data on authorship, more are taken from journals on the internet as a support for authorship. This study describes Nyai Siti Walidah or commonly known as Kyai Ahmad Dahlan and also Nyai Khairiyah Hasyim as two figures driving women in the world of education in Indonesia. As for Nyai Siti Walidah, she founded a women's organization, which is active in the fields of religion, social, economics, and education. The organization founded by Nyai Ahmad Dahlan was named Aisyiyah. Likewise Nyai Khairiah in establishing her madrasah, she taught ethics, skills, knowledge, religious knowledge, and other sciences, as a provision for women in the future. While the nature of this study is an analytical description, namely presenting data from research objects to be interpreted so that the results of this study indicate that the movement carried out by Siti Walidah and Khairiyah Hasyim in fighting for women's education actually started from their intentions and also their aspirations for such a desire. great for elevating the dignity of women at that time.